Roxadustat for Treating Anemia in Patients with CKD Not on Dialysis: Results from a Randomized Phase 3 Study - Fishbane, Steven (J Am Soc Nephrol, 2021)
BACKGROUND: Current anemia therapies for patients with non–dialysis-dependent CKD may require injection and medical visits. Roxadustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor, stimulates erythropoiesis and improves iron homeostasis. METHODS: In this double-blind phase 3 study, we randomized patients with non–dialysis-dependent CKD stages 3–5 and hemoglobin <10.0 g/dl (1:1) to thrice-weekly 70-mg oral roxadustat or placebo. Doses were titrated throughout the study based on hemoglobin levels. The primary efficacy end point was mean change from baseline in hemoglobin averaged over weeks 28–52 versus placebo, irrespective of rescue therapy use. We assessed patients for adverse events. RESULTS: The study included 2781 patients, 1393 who received roxadustat and 1388 who received placebo. Mean baseline hemoglobin was 9.1 g/dl for both groups. The mean change in hemoglobin from baseline was 1.75 g/dl (95% confidence interval [95% CI], 1.68 to 1.81) with roxadustat versus 0.40 g/dl (95% CI, 0.33 to 0.47) with placebo, (P<0.001). Among 411 patients with baseline elevated high-sensitivity C-reactive protein, mean change in hemoglobin from baseline was 1.75 g/dl (95% CI, 1.58 to 1.92) with roxadustat versus 0.62 g/dl (95% CI, 0.44 to 0.80) with placebo, (P<0.001). Roxadustat reduced the risk of red blood cell transfusion by 63% (hazard ratio, 0.37; 95% CI, 0.30 to 0.44). The most common adverse events with roxadustat and placebo, respectively, were ESKD (21.0% versus 20.5%), urinary tract infection (12.8% versus 8.0%), pneumonia (11.9% versus 9.4%), and hypertension (11.5% versus 9.1%). CONCLUSIONS: Roxadustat effectively increased hemoglobin in patients with non–dialysis-dependent CKD and reduced the need for red blood cell transfusion, with an adverse event profile comparable to that of placebo. CLINICAL TRIAL REGISTRY NAME AND REGISTRATION NUMBER: Safety and Efficacy Study of Roxadustat to Treat Anemia in Patients With CKD, Not on Dialysis, NCT02174627